Integrated toxicity evaluation of metals in sediments of Jiaozhou Bay (China): Based on biomarkers responses in clam Ruditapes philippinarum exposed to sediment extracts. (June 2018) - Lin, Yufei; Liu, Qunqun; Meng, Fanping; Lin, Yichen; Du, Yongxiang
Abstract: To evaluate the integrated toxicity of metals in sediments of Jiaozhou Bay, we exposed clam ( Ruditapes philippinarum ) to sediments extracts obtained using of sediment extraction with deionised water adjusted to pH 4 which simulated the weak acidity in the digestive juice of clams and tested the selected biomarkers responses in clams for exposure over 15 days. At the same time, the contents of metals in sediments were assessed with method of the mean sediment quality guideline quotient (SQG-Q). The integrated biomarker response version 2 (IBRv2 ) was used to assess the integrated toxicity induced by metals in sediment extracts based on biomarkers response in clams: the results demonstrated that site S7 located in the mouth of Nanxin'an River show higher IBRv2 values compared to the other sites. The IBRv2 values exhibited the good consistency with SQG-Q values. Highlights: All sites sediments metals exhibited moderate potential toxicity based on SQG-Q. Selected biomarkers showed strong response to different sites sediment extracts. Metals integrated toxicity of different sites can be distinguished by IBRv2 values. The evaluation results of IBRv2 were well correlated with SQG-Q.